A woman's worth: Analyzing the sexual objectification of Black women in music videos - Ward, L. Monique; Rivadeneyra, Rocio; Thomas, Khia; Day, Kyla; Epstein, Marina (The sexualization of girls and girlhood: Causes, consequences, and resistance, 2013)
One arena where images of sexually objectified women are especially prevalent is the world of music videos. Music videos represent an important area of study, both because of their popularity with younger viewers (Ashby & Rich, 2005) and because love and sex predominate as themes (Andsager & Roe, 1999; Arnett, 2002). What we seek to do here is to take a closer look at the nature and impact of the portrayal of women in music videos, focusing, in particular, on sexually objectifying images. How frequently do objectifying images occur? What messages about femininity do these images convey to girls? What is their demonstrated impact on girls and young women? Given the current popularity of rap and hip-hop music, we focus our attention on their portrayals of African American women. We address these issues via four pathways. First, we summarize findings from existing research concerning the nature of gender portrayals in music videos. Second, we turn our attention to African American artists and summarize findings about the images of black women in music videos. Third, we present new data from an analysis we conducted of the sexual content in black music videos, providing both quantitative and thematic analyses. Finally, we summarize findings about the demonstrated impact of music video exposure on young viewers' gender beliefs and body image concerns. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Keywords: Blacks; Human Females; Music; Myriam; Objectification; Sex Roles